2016
DOI: 10.1002/stvr.1609
|View full text |Cite
|
Sign up to set email alerts
|

Prioritizing manual test cases in rapid release environments

Abstract: Summary Test case prioritization is an important testing activity, in practice, specially for large scale systems. The goal is to rank the existing test cases in a way that they detect faults as soon as possible, so that any partial execution of the test suite detects the maximum number of defects for the given budget. Test prioritization becomes even more important when the test execution is time consuming, for example, manual system tests versus automated unit tests. Most existing test case prioritization te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 37 publications
1
32
0
Order By: Relevance
“…Hemmati et al [18] investigated the effectiveness of three black-box TCP techniques on Firefox before and after the transition to rapid releases. The authors concluded that 5 HBTP is far more effective than other comparable techniques in rapid releases, although the same conclusion does not hold in traditional development environments.…”
Section: Related Work 221 Test Prioritization In CI Environmentsmentioning
confidence: 99%
See 4 more Smart Citations
“…Hemmati et al [18] investigated the effectiveness of three black-box TCP techniques on Firefox before and after the transition to rapid releases. The authors concluded that 5 HBTP is far more effective than other comparable techniques in rapid releases, although the same conclusion does not hold in traditional development environments.…”
Section: Related Work 221 Test Prioritization In CI Environmentsmentioning
confidence: 99%
“…Therefore, the tests that failed in previous releases have a much higher probability of failing again in the current release. This is perhaps due to the recency of historical knowledge, which explains its effectiveness in a rapid-release environment, rather than other changes in the development process [18]. There is also a number of studies that are particularly focused on HBTP.…”
Section: Related Work 221 Test Prioritization In CI Environmentsmentioning
confidence: 99%
See 3 more Smart Citations